Understanding engineered nanomaterial skin interactions and the modulatory effects of ultraviolet radiation skin exposure. (3rd October 2013) - Jatana, Samreen; DeLouise, Lisa A.
Abstract : The study of engineered nanomaterials for the development of technological applications, nanomedicine, and nano‐enabled consumer products is an ever‐expanding discipline as is the concern over the impact of nanotechnology on human environmental health and safety. In this review, we discuss the current state of understanding of nanomaterial skin interactions with a specific emphasis on the effects of ultraviolet radiation (UVR) skin exposure. Skin is the largest organ of the body and is typically exposed to UVR on a daily basis. This necessitates the need to understand how UVR skin exposure can influence nanomaterial skin penetration, alter nanomaterial systemic trafficking, toxicity, and skin immune function. We explore the unique dichotomy that UVR has on inducing both deleterious and therapeutic effects in skin. The subject matter covered in this review is broadly informative and will raise awareness of potential increased risks from nanomaterial skin exposure associated with specific occupational and life style choices. The UVR‐induced immunosuppressive response in skin raises intriguing questions that motivate future research directions in the nanotoxicology and nanomedicine fields. WIREs Nanomed Nanobiotechnol 2014, 6:61–79. doi: 10.1002/wnan.1244 This article is categorized under: Therapeutic Approaches and Drug Discovery > Emerging Technologies Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials